Fish and invertebrate length frequencies of three bottom trawl hauls in 2022, southern North Sea - Floeter, Jens (PANGAEA, 2023)
During a MARSYS student training cruise (HE600) three bottom trawl hauls were conducted on 2022 June 3., 7. and 10. in the southern North Sea. The length frequency data originate from bottom trawl hauls, conducted with the Schollennetz from RV Heincke. The trawl ground rope was approx. 17 m, the vertical opening approx. 2 m and the cod end mesh size 1 cm. Tow duration was recorded for effort standardization. Fish size was measured to the next lower centimeter (“cm below”). Fish and invertebrate catch per unit of effort and biomass of three bottom trawl hauls in 2022, southern North Sea.
Keywords: bottom trawl survey; fish abundance; North Sea; size distribution